'Alternate versions of the same reality': adapting Under the Dome as an sf television series. (June 2017) - Brown, Simon
Abstract : This article examines the CBS adaptation of Stephen King's 2009 novel Under the Dome as an example of a successful adaptation of a King text. It begins by considering the fact that King adaptations have often proved to be disappointing to either King or genre fans and contends that part of the problem is the difficulty of both defining and capturing what it is that makes King's writing so popular, before arguing that the essential success of King's texts lies in their focus upon character prior to elements of the supernatural being engaged. It then discusses Under the Dome as a King story adapted, with his input, into a long-format, multi-season, complex television drama as part of a deliberate strategy on the part of CBS to use sf to build a mainstream summer audience and draw cult television audiences back to the network. Finally, this article contends that it is precisely this marshalling of King's story to fit the new paradigm of 'complex television' and to appeal to both mainstream and cult audiences that enables Under the Dome to capture, if not all the events, then certainly the spirit of King's novel.